IMPROVE QUALITY APPLING METHODOLOGY ANSWER SURFACE AND NEURAL NETWORKS - Del Carpio Gallegos, Javier (2006)
This article show an abstract of research proyect doing by the manager y collaborators of proyect, show the advantages of use neural networks opposite another techniques about improve quality, to get mean error squares more lows (MSE).